2014
DOI: 10.1186/s13046-014-0102-9
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated arginine deiminase synergistically increases the cytotoxicity of gemcitabine in human pancreatic cancer

Abstract: BackgroundPancreatic ductal adenocarcinoma has proven to be one of the most chemo-resistant among all solid organ malignancies. Several mechanisms of resistance have been described, though few reports of strategies to overcome this chemo-resistance have been successful in restoring sensitivity to the primary chemotherapy (gemcitabine) and enter the clinical treatment arena.MethodsWe examined the ability of cellular arginine depletion through treatment with PEG-ADI to alter in vitro and in vivo cytotoxicity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…Previous work has identified changes in the GEM pathway that occur as a result of arginine starvation induced by ADI-PEG20 (12,44,45). This study confirmed that the degradation of arginine from ASS1-deficient, arginine auxotrophic cancers stabilizes c-Myc (19), and that the addition of DTX facilitates c-Myc translocation to the nucleus, which results in increased hENT1 surface expression.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Previous work has identified changes in the GEM pathway that occur as a result of arginine starvation induced by ADI-PEG20 (12,44,45). This study confirmed that the degradation of arginine from ASS1-deficient, arginine auxotrophic cancers stabilizes c-Myc (19), and that the addition of DTX facilitates c-Myc translocation to the nucleus, which results in increased hENT1 surface expression.…”
Section: Discussionsupporting
confidence: 78%
“…Effect of acute and chronic arginine starvation on the GEM pathway in ASS1 À cell lines Based on previous findings, alterations in the pyrimidine pathway have been seen in response to arginine starvation (12,44,45). Using our established model of arginine starvation in sarcoma of acute and long-term ADI-PEG20 treated (LTAT), the alterations in the GEM pathway were examined ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy inhibitor chlorquine accelerated ADI-PEG20 induced cell death in vitro Pancreatic cancer 1. Inhibited growth and induced apoptosis of ASS1-ve pancreatic cancer cell lines in vitro (about 80% pancreatic cancer samples tested in the study were ASS1-ve) [ 166 , 167 ] 2. Suppressed growth of subcutaneously implanted tumor in athymic nude mice.…”
Section: Arginine Starvation As An Anti-cancer Strategymentioning
confidence: 99%
“…The fundamental difference of cell cycle modulations in normal and malignant cells should be exploitable as a means of selective demise of tumor cells and ADI, in combination with other anti-cancer chemotherapeutic agents, which can be a potential strategy to improve chemosensitization against tumor cells. 115118 …”
Section: Arginine Deiminasementioning
confidence: 99%